Determinants of mobile phone waste recycling and end-of-life management in Johor - Shah, Gautam Lalit (2017)
Growing development in the telecommunications industry, along with frequent purchases, upgrading and increased ownership of mobile phones (MPs) have indirectly contributed to the global increase in e-waste generation, along with future pile-ups of used MP units and accessories. An improper end-of-life (EOL) management of MPs further exacerbated environmental degradation associated with their hazardous waste components. The increasing number of new MP purchases and service subscriptions, especially in Johor had made it relevant to study how the MP usage trend and its EOL management amongst consumers and sellers could affect future stockpiling and e-waste disposal. This study also analyzed the urban and non-urban respondents‘ willingness to pay (WTP) for a green MP or participate (WTPar) in a recycling program as well as their opinions on MP-related policy and recycling facilities. It involved a randomly selected sample of 1200 MP users and 110 sellers around urban Johor Bahru and non-urban areas (i.e., Muar and Kota Tinggi). Mean comparison or analysis of variance (ANOVA), bivariate analysis, and linear regression were used to determine associations between socio-economic background and purchasing activity as well as willingness-to-participate in a recycling program between the groups. Results indicated that on average, urban consumers chose price in making purchases, owned more MP units and kept them as spares, thus implying the stockpiling problem. Based on Kendall's tau coefficient, willingness to participate in a recycling program and pay more for a green MP differed according to socio-economic and locational factors (i.e., p < 0.01 or significant at 99% confident level). Majority, especially the non-urban respondents, were highly supportive of incentives and rebates, along with improved accessibilities and increased number of recycling facilities in promoting a more sustainable EOL management of MPs. The study provides a new insight in integrating locational and socio-economic factors, as well as MP usage, pricing, purchasing behavior, and convenience with current and future MP‘s EOL management system and policy framework.